Sedimentary record of PAH in a tropical coastal lagoon form the Gulf of Mexico - Calva B., Laura Georgina; V. Botello, Alfonso; Wong Chang, Irma (HIDROBIOLÓGICA, 2017)
Sediment core samples were collected in Sontecomapan coastal laggon, Veracruz; in the Gulf of Mexico on August 1992. The concentrations of 15 priority Polycyclic Aromatic Hydrocarbons (PAH) were analyzed by gas chromatography, using capillary columns of high resolution and flame ionization detection (GD-FID) to reconstruct a history of PAH contaminant input into the lagoon. The average values of PAH registered for core "A" (with fresh water influence) were from 9.76 µg/g; core "B" (in the zone where fresh and marine water mix) registered the highest concentrations with 16.80 µg/g; and core "C" (marine influence) demostrated the lowest levels with 8.13 µg/g. Vertical profiles of PAH concentrations were characterized by a maximum at depth between 1-5 cm and by almost constant descent levels at depth of 6 to 15 cm. With regard to the hierarchical behavior of the individual compounds of PAH in all cores, in descending order, they were: Chrysene > Indenol(1,2,3-c,d)pyrene > Benzo(a)anthracene > Benzo(b)fluoranthene > Benzo(k)fluoranthene > Benzo(a)pyrene. The aromatic with 4 to 6 rongs predominated in the concentrations of PAH, which suggests the origin of these compounds is ue to the pyrolysis of organic material and fossil fuels. The higher aromatics predominated due to their higher persistence. PAH goes into system through motor boat activity, river discharges, by tidal action from the coast and from atmospheric transport.